Analysis Of Phytochemical Compounds, Antioxidant And Anti-Inflammatory Activities Of Methanolic Extract Of Ruthana Date Fruits (Phoenix Dactylifera) - Faris, Alsarayrah Nosiba Atallah (2023)
Ruthana date fruit, one of the finest types of dates, contains various nutrients and phytochemical compounds important for human health. Therefore, it is important to highlight the analysis of the medicinal value of these fruits in studies related to clinical nutrition. In this study, phenols, and flavonoid contents of date fruit methanolic extract (DFME) were measured due to their importance in inhibiting activities of free radicals. The antioxidant activities of the extract were evaluated by several analytical methods, which include 2,2-Diphenyl-1-Picrylhydrazyl radical scavenging assay (DPPH), Ferric reducing antioxidant power (FRAP), 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging assay (ABTS+), and nitric oxide radical scavenging assay (NO). In addition, the anti-inflammatory effects of DFME were studied in vitro using albumin denaturation, and red blood cell membrane stabilization assays. The results showed that DFME contains a high value of polyphenol compounds.